Electrodeposited reduced graphene oxide as a highly efficient and low-cost electrocatalyst for vanadium redox flow batteries - Nia, Pooria Moozarm; Abouzari-Lotf, Ebrahim; Woi, Pei Meng; Alias, Yatimah; Ting, Teo Ming; Ahmad, Arshad; Che Jusoh, Nurfatehah Wahyuny (Elsevier, 2019)
An electrochemically reduced graphene oxide was grown on carbon felt surface in a simple one-step electrodeposition process of graphene oxide and it was employed as a positive electrocatalyst of vanadium redox flow battery. The electrodeposited graphene-based nanocomposite on carbon felt presented outstanding electrochemical redox reversibility toward vanadium redox couple. Based on the cyclic voltammetry data and electrochemical impedance spectroscopy curves, the modified composite electrode possesses a huge amount of oxygen functional groups, high surface area, high electrical conductivity and excellent stability in compared to the pristine carbon felt electrode. The prepared electrode showed promising performance for vanadium redox flow battery as the energy efficiency was significantly enhanced by 12% at current density of 60 mA cm−2. This superior performance was probably due to the increase in the surface sites and fast electron transfer rate of the reduced graphene oxide.